2023
DOI: 10.1002/app.53592
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and modeling studies of IPDI‐based polyurea elastomers – The role of hard segment fraction

Abstract: Segmented polyureas (PUa) are industrially important class of polymers widely used in coatings, sealant, and adhesive applications. Here, we report synthesis, characterization, and modeling of Isophorone Diisocyanate-Diethyl-Toluene-Diamine-Polyether amine (IPDI-DETDA-PO PUa) with varied hard segment contents of 20, 30, and 40 weight percent. For each of the three materials, we study its structure and phase behavior using FTIR, DSC, and TEM, and clearly show the presence of microphase separation between the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Given the relatively low mass fraction of the added nanoparticles (only up to 1.5%), we assumed that they were ultimately dispersed within the two phases and not forming a new phase by themselves. Thus, no additional parallel branch was introduced, consistent with our prior work [19]. Consequently, each polymer was characterized by six model parameters, encompassing two characteristic moduli (often called plateau modulus) (𝐸 , and 𝐸 , ), two relaxation characteristic times (𝜏 , and 𝜏 , ), and two power-law exponents (𝛼 and 𝛼 ).…”
Section: Modeling 231 Fractional-order Maxwell Gel Modelmentioning
confidence: 91%
See 3 more Smart Citations
“…Given the relatively low mass fraction of the added nanoparticles (only up to 1.5%), we assumed that they were ultimately dispersed within the two phases and not forming a new phase by themselves. Thus, no additional parallel branch was introduced, consistent with our prior work [19]. Consequently, each polymer was characterized by six model parameters, encompassing two characteristic moduli (often called plateau modulus) (𝐸 , and 𝐸 , ), two relaxation characteristic times (𝜏 , and 𝜏 , ), and two power-law exponents (𝛼 and 𝛼 ).…”
Section: Modeling 231 Fractional-order Maxwell Gel Modelmentioning
confidence: 91%
“…The synthesis of the PUa-Neat materials is described in detail in our earlier paper [19]. We used isophorone diisocyanate (IPDI)-Vestanat from Evonik Corporation, Pisca-taway, NJ, USA; Jeffamine T5000 and D2000 polyetheramines from the Huntsman Corporation, The Woodlands, TX, USA; and the diethyltoluene diamine (DETDA) (Lonzacure) chain extender from Lonza, Morristown, NJ, USA.…”
Section: Polymer Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…In a study by D.A. Tzelepis et al [33], several polyureas were synthesized with the same molecular weight of the soft segments but varying weight fractions of the hard segments. The structure of the polyurethanes was characterized using differential scanning calorimetry (DSC) and a transmission electron microscope (TEM) which revealed that the three polymers had almost the same Tg.…”
Section: Structural Features Of Polyurea Moleculesmentioning
confidence: 99%